2003
DOI: 10.1177/030089160308900312
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Cerebral Metastases from Non-Small Cell Lung Cancer

Abstract: Our findings correspond well with those reported in the literature and suggest that surgical resection of single brain metastasis in patients with non-small cell lung cancer can improve survival over conservative management. Furthermore, surgical treatment of the primary tumor and the single brain metastasis, combined or not with radiotherapy and chemotherapy, represents an approach that merits further investigation with more patients and a prospective longitudinal design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…However, the nodal involvement status did not appear as a significant factor in this situation, as previously reported (Fig. 2) [9,11,12,19,31,32]; thus, the recommendation to exclude patients with N2 or even N3 involvement from combined resection may be debated [41].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, the nodal involvement status did not appear as a significant factor in this situation, as previously reported (Fig. 2) [9,11,12,19,31,32]; thus, the recommendation to exclude patients with N2 or even N3 involvement from combined resection may be debated [41].…”
Section: Discussionmentioning
confidence: 60%
“…Previously reported series of patients with resected brain metastases from lung cancer are mostly based on selected groups [8][9][10][11][12][13][14][15][16], treated with various adjuvant modalities [9][10][11][12][13][14][15][16][17][18][19][20][21], at different times of the development of cancer [9,10,11,[22][23][24][25][26][27], and definite conclusions on prognostic factors and therapeutic options are thus difficult to assess. In contrast to the dogma that distant spread precludes thoracic surgery, a small number of patients with synchronous brain metastases may benefit from combined resection of both the primary and the metastatic site [9,11,12,20,[27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Clinicopathological feature analyses have revealed that, for NSCLC patients presenting with brain-specific metastasis alone, metastatic lesion resection or other adjuvant therapies may improve quality of life and prolong survival time (7–9). Therefore, identifying patients with a high risk of brain-specific metastasis following lung cancer resection is clinically significant for predicting the prognosis and selecting the most appropriate adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This patient is alive and disease free 18 months following presentation. It is accepted practice today to consider selected patients with solitary intracranial deposits for resection [ 39 - 41 ]. Also it has been suggested repeatedly that a survival benefit may be achieved by surgical treatment of solitary extracranial spread of NSCLC [ 42 - 46 ].…”
Section: Discussionmentioning
confidence: 99%